Assessment of Crop Site Suitability of Under-Utilized Land Using Multi-Criteria Decision and Geospatial Techniques - Nor Aizam Adnan; Aida Firdaus MN Azmi; Raseetha, Vani Siva Manikam; Siti Maslizah Abdul Rahman; Ismail Rakibe; Wan Edura Wan Rashid; Ahmad Rosly Abbas; Nur Iffika Ruslan; Aainaa Suhardi (International Journal of Integrated Engineering, 2024)
Site suitability study for agriculture or crops are an important technique in deciding potential agricultural types, planning and activities. Site suitability analysis is an assessment of an area to determine its appropriateness for a particular use of the land (such as growing varieties of crop) in a particular location. Assessment of crops site suitability can be done from various approaches and one of the mostly used approach is utilizing geographical information system (GIS) geospatial analysis based on a multi-criteria decision-making method. A widely used multi-attribute technique that has been incorporated into the GIS-based crop site suitability procedure is the Analytical Hierarchy Process (AHP) for multiple factors assessment integrating physical (slope and topography) and socio-economic factors (land use/land cover, distance from road and water bodies localities). This research is conducted to analyse land criteria factors (i.e., physical, and socio-economic) to assess crop site suitability for under-utilized land in selected districts of the Selangor state. The findings show that the proposed method is able to outline the crop site suitability area in Selangor based on four different suitability categories of not suitable, less suitable, moderately suitable and highly suitable. The integration between GIS and AHP significantly provides an effective approach in assessing crop site suitability for better land use/land cover and agriculture management and production.